Punishment and democracy: three strikes and you're out in California - Zimring, Franklin E. (Studies in crime and public policy, 2001)
The authors provide a comprehensive treatment of the politics and impact of 'get tough' criminal sentencing legislation in the United States. The book includes a study of the celebrated California 'three strikes' law.